ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DENGAN PENDEKATAN MODEL- ELICITNG ACTIVITIES - Risna Maryanasari; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to describe and analyze students' mathematical connection skills where this study uses the Model-Eliciting Acivities (MEAs) approach with material systems of two-variable linear equations (SPLDV). this study uses a classroom action research (PTK) approach which consists of four stages, namely 1) planning. 2) implementation / action, 3) observation / observation and 4) reflection. With subjects of class VIII as many as 21 students. The technique used is data collection in the form of test questions, interviews, and documentation. The analysis technique used is by presenting data and drawing conclusions. The results of the research are based on the results of the students' pretest and posttest where the pretest before the students get the action and posttest after the students get the action, where from the results students get the action using the MEAs approach better than before using the action.